2020
DOI: 10.1016/j.chom.2019.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Rabies Virus Glycoprotein Reveals pH-Dependent Conformational Changes and Interactions with a Neutralizing Antibody

Abstract: Highlights d RABV-G ecto-domain protein structure is revealed using a fusion-loop substitution strategy d Crystal structures of RABV-G at both basic and acidic pHs are solved d Structural comparison reveals basis of pH-dependent structural transitions in RABV-G d Complex structure shows 523-11 antibody binds a bipartite epitope for neutralization

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
96
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(107 citation statements)
references
References 62 publications
8
96
2
1
Order By: Relevance
“…Despite belonging to evolutionary seemingly unrelated virus families, the arrangement and structure of their individual domains are conserved (Fig. 1, A and B), but high-resolution structures for the prefusion form are only available for two rhabdovirus glycoproteins (12,13). In the postfusion conformation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Despite belonging to evolutionary seemingly unrelated virus families, the arrangement and structure of their individual domains are conserved (Fig. 1, A and B), but high-resolution structures for the prefusion form are only available for two rhabdovirus glycoproteins (12,13). In the postfusion conformation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There is structural evidence supporting the hypothesis that SARS-CoV-2 virus is a nicotinic agent. The recently reported X-ray structure of the RABV glycoprotein (G) ectodomain [49] shows that the region corresponding to the neurotoxin-like peptide is exposed at the G surface, in agreement with the fact that this region is part of the major antigenic region II of RABV [50]. The recently published cryo-EM structure of the trimeric SARS-CoV-2 spike (S) protein [51,52] revealed an insertion with respect to that of SARS-CoV-1, in a loop that is disordered in the reported structure, and which has a polybasic sequence that corresponds to a furin site.…”
mentioning
confidence: 99%
“…Recent studies have confirmed the crystal structures of RABV G and its interaction with neutralizing antibodies (Hellert et al, 2020;Yang et al, 2020). Residues from G333-G350 of ectodomain from three strains (CVS-11, Flury, and SAD-B19) are observed to bond to antibody 523-11 (Yang et al, 2020).…”
Section: Figure 5 | (A)mentioning
confidence: 77%